Efficacy of acupuncture intervention for the treatment of Gouty Arthritis: a Case Report - Om Prakash, Deepika; Mangaiarkarasi, N.; Manavalan, N. (Indian Journal of Integrative Medicine, 2022)
Background: Gout is a disorder of purine metabolism in which a high serum uric acid is found and deposit of urate crystals within joints causing exquisite pain and tenderness. Method: A 47 years male was pre-diagnosed with gouty arthritis for the past 6 months having severe bilateral pain on both big toes associated with swelling and difficulty in walking. This case study was done to investigate the effectiveness of acupuncture for managing pain and to down-regulate the uric acid level in a patient with gouty arthritis. Result: Baseline and post data were assessed on day 0 and day 11 of intervention. After 11 days of intervention patient’s pain intensity and serum uric acid level were reduced. Conclusion: This result has shown that acupuncture may be effective in the management of gouty arthritis